Success Factors For Small And Medium Industries Based On Creative Industries - Fitria Ardiana (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
The purpose of this study was to determine the effects of entrepreneurial characteristics, interest in entrepreneurship, business networks, promotion and government support for the success of creative industries based in Magelang Regency. The sampling technique uses non-probability sampling with a convenience sampling approach, as many as 100 entrepreneurs. Data collection techniques using a questionnaire or questionnaire. Data were analyzed using Partial Least Square with reflective measurement models for each latent variable in the study . The suggestion from this research is that entrepreneurs can increase theircourage in taking risks and create interesting and creative things and be more active in participating in programs organized by the government to increase business success and the government can give awards or prizes to entrepreneurs who actively participate in government programs.